PKM Group of Ecoprint Craftsmen Based on Digital Marketing in Bajong, Purbalingga: PKM Kelompok Pengrajin Ecoprint Berbasis Digital marketing di Bajong, Purbalingga - Novian Adi Prasetyo; Muhammad Lulu L. Usman; Giovanny B. Kristianto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The Ecoprint batik making group in Bajong Village, Bukateja Subdistrict, has the potential to support the community's economy with the concept of environmentally friendly products. However, group partners experience obstacles in increasing sales due to a lack of knowledge and sales management as well as a lack of marketing strategy. Apart from that, the location of the owner's house is not strategic, and the lack of financial records, stock and raw materials are obstacles in business development. The main problem faced by partners is low turnover due to minimal use of technology in marketing strategies, lack of transaction and stock management, and limited production equipment. The solution proposed in this Student Activity Research (PKM) involves various stages, including training in the use of technology, improving sales management, procurement of production equipment, and product diversification based on market analysis. By implementing these solutions, there have been an increase in the income of Ecoprint batik group partners. The results of this PKM are disseminated through national journals, electronic mass media and online videos, providing wider benefits and increasing public awareness about environmentally friendly products.